Influence of laser treatment parameters on the mode I strain energy release rate of aluminum double cantilever beam joints. (June 2018) - Moroni, F.; Musiari, F.; Romoli, L.; Pirondi, A.
Abstract: Surface texturing produced by laser ablation is an efficient and effective technology for treating substrates to improve adhesive bond strength. In the literature, its effect has been extensively studied for different adherends materials, adhesives and laser sources. Laser ablation produces both morphological and chemical modifications of the surfaces, promoting mechanical interlocking and chemical bonding between the adhesive and the substrates. In this work, the effect of pulsed Yb-fiber laser ablation over the quasi-static mode I fracture energy of Double Cantilever Beam (DCB) aluminum bonded joints has been assessed for different combinations of processing parameters, with the aim of optimizing the treatment for industrial purposes. The mechanical tests show that the treatment becomes effective when a laser energy density threshold is overcome. On the other hand, a further increase in the energy density leads to a slight reduction of the joints fracture energy. This is related to the viscosity of the adhesive and to the high roughness produced by high energy treatments, resulting in the presence of air bubbles in the adhesive layer. In order to understand this phenomenon, the treated surfaces are characterized from the morphological point of view using a 3D optical profiler and SEM analysis.